Prevalence of left atrial thrombus in patients with non-valvular atrial fibrillation - Minno, Matteo Nicola Dario Di; Ambrosino, Pasquale; Russo, Antonio Dello; Casella, Michela; Tremoli, Elena; Tondo, Claudio (Thrombosis and Haemostasis, 2016)
We performed a meta-analysis about the prevalence of left atrial thrombus (LAT) in patients with atrial fibrillation (AF) undergoing trans-esophageal echocardiography (TEE). Studies reporting on LAT presence in AF patients were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases and the pooled LAT prevalence was evaluated as weighted mean prevalence (WMP). Seventy-two studies (20,516 AF patients) showed a LAT WMP of 9.8 % (95 %CI: 7.6 %-12.5 %). LAT presence was associated with a higher age (mean difference: 2.56, 95 %CI: 1.49–3.62), and higher prevalence of female gender (OR: 1.35, 95 %CI: 1.04–1.75), hypertension (OR: 1.78, 95 %CI: 1.38–2.30), diabetes mellitus (OR: 1.86, 95 %CI: 1.33–2.59) and chronic heart failure (OR: 3.67, 95 %CI: 2.40–5.60). Overall, LAT patients exhibited a higher CHADS2-score (mean difference 0.88, 95 %CI: 0.68–1.07) and a higher risk of stroke/systemic embolism (OR: 3.53, 95 %CI: 2.24–5.56) compared with those without LAT. A meta-regression showed an inverse association between LAT prevalence and the presence of anticoagulation (Z-value: −7.3, p< 0.001). Indeed, studies in which 100 % of patients received oral anticoagulation reported a 3.4 % WMP of LAT (95 %CI: 1.3 %–8.7 %), whereas studies in which 0 % of patients received anticoagulation showed a LAT WMP of 7.4 % (95 %CI: 2.3 %–21.5%). Our data suggest that LAT is present in ≈10 % of AF patients, and is associated with a 3.5-fold increased risk of stroke/systemic embolism. Interestingly, LAT is also reported in some of patients receiving anticoagulation. The implementation of the screening of LAT in AF patients before cardioversion/ablation could be useful for the prevention of vascular events.
Keywords: Atrial fibrillation; left atrial thrombus; transesophageal echocardiography